Micropropagation of Stevia Plant from Nodal Segments - Karim, MA; Jannat, R; Rahman, MS; Haque, MS (Progressive Agriculture, 2013)
The experiment was conducted to develop and establish a reproducible protocol for plantlet regeneration in Stevia. Nodal cutting explants were cultured in Murashige and Skoog (MS) medium supplemented with different concentrations and combinations of ?-Napthaleneacetic acid (NAA) and 6-Benzylamino purine (BAP). The combination of NAA at 1.0 mgl-1 and BAP at 1.0 mgl-1 resulted in the highest percentage (100%) of callus initiation. The maximum shoot regeneration and development of shoot was observed at the same combination. The developed shoots from nodal cuttings, upon transfer to the MS medium containing indole butyric acid (IBA) at 0.1mgl-1 resulted in best rooting within 8 days. DOI: http://dx.doi.org/10.3329/pa.v19i2.16914 Progress. Agric. 19(2): 21 - 26, 2008